2016
DOI: 10.1098/rstb.2015.0124
|View full text |Cite
|
Sign up to set email alerts
|

A trip down memory lane about sex differences in the brain

Abstract: One contribution of 16 to a theme issue 'Multifaceted origins of sex differences in the brain'.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 71 publications
1
27
0
Order By: Relevance
“…Estrogens and stress also interacted in a regionally specific manner in the PFC, in that cortically-projecting PFC neurons, which showed no dendritic changes after CRS in either intact or ovariectomized (OVX) animals, displayed a CRS-induced increase in spine density in OVX animals but not in intact females with circulating estradiol; yet amygdala-projecting PFC neurons showed CRS-induced spine density that was enhanced in intact females to accompany the dendrite expansion (Shansky et al 2010). Regarding function, as shown by lesion studies, contralateral prefrontal to amygdala projection is key to the ability of acute foot shock stress to impair eyeblink conditioning in female rats, whereas male rats normally show enhanced conditioning after the same footshock stress, as is discussed below (Shors 2016). …”
Section: Sex Differences Beyond the Hippocampus: Some Examplesmentioning
confidence: 98%
See 2 more Smart Citations
“…Estrogens and stress also interacted in a regionally specific manner in the PFC, in that cortically-projecting PFC neurons, which showed no dendritic changes after CRS in either intact or ovariectomized (OVX) animals, displayed a CRS-induced increase in spine density in OVX animals but not in intact females with circulating estradiol; yet amygdala-projecting PFC neurons showed CRS-induced spine density that was enhanced in intact females to accompany the dendrite expansion (Shansky et al 2010). Regarding function, as shown by lesion studies, contralateral prefrontal to amygdala projection is key to the ability of acute foot shock stress to impair eyeblink conditioning in female rats, whereas male rats normally show enhanced conditioning after the same footshock stress, as is discussed below (Shors 2016). …”
Section: Sex Differences Beyond the Hippocampus: Some Examplesmentioning
confidence: 98%
“…A morphological correlate of this in the hippocampus is the finding that acute stress inhibits estrogen-depending spine formation in CA1 neurons of the hippocampus, whereas the same acute stressors enhance spine density in male CA1 neurons, possibly by increasing testosterone secretion (Shors et al 2001) upon which spine formation in the male CA1 is dependent (Leranth et al 2003). Neonatal masculinizaton of females made them response positively, like genetic males, to the shock stressor (Shors 2016) Moreover, in females, depending on reproductive status and previous experience, the negative stress effect was altered, e.g., it was absent in mothers and virgin females with experience with infants (Shors 2016). …”
Section: Sex Hormone Actions Beyond the Hypothalamus: Focus On The Himentioning
confidence: 99%
See 1 more Smart Citation
“…Opposite changes in hippocampal synaptic density correlate with the divergence in behavioural responding, so there appears to be a connection between neuroanatomy and behaviour (reviewed in [65]). But as Shors [64] goes on to point out, the divergence in response to stress occurs only during a limited time in the female reproductive cycle, proestrus, a time of high circulating oestradiol, and she makes a case for the importance of considering life stage in any discussion of sex differences. This is an important caveat and its truth is borne out in studies of humans across the lifespan, which show a convergence in the size of specific nuclei in older adults compared with younger [66].…”
Section: (C) Compensation and Convergence In Sexually Dimorphic Behavmentioning
confidence: 99%
“…Studies of learning provide a particularly interesting perspective on how the sexes can differ in both the neurophysiological underpinnings and the expression of a behaviour. In this issue, Shors [64] takes a trip down memory lane to review her 20 year journey of deciphering how males and females learn and how that learning is impacted by stress. Using the conditioned eye-blink task, which is attractive for not being confounded by hunger, fear or motivation, she observed that males improved under stressful conditions whereas female performance deteriorated.…”
Section: (C) Compensation and Convergence In Sexually Dimorphic Behavmentioning
confidence: 99%